Untrodden ground : how Presidents interpret the Constitution - Bruff, Harold H., 1944- (University of Chicago Press, 2015)
The most important individual interpreter of the United States Constitution is the President. Presidents both direct and are directed by the stream of American history. In this book, Harold Bruff shows how Presidents have formed constitutional law by behavior that sets or alters precedents. Although Presidents ordinarily obey both court judgments and explicit statutory commands, presidential interpretations of the Constitution are ultimately independent of the views of the other two branches of government.